Effect of the aging process on the yield ratio of 6013 aluminum alloy extruded profile - Rui-fang ZHANG; Ji XU; Xin-ming FENG; Fan ZHAO; Zhi-hao ZHANG (工程科学学报, 2023)
Because of its high strength and good fracture toughness, 6013 aluminum alloy is widely used in auto and aircraft parts, such as the outer hood, outer decklid, and outer fuselage skin. An aluminum alloy must have good plastic forming ability in forming auto and aircraft parts and must have high deformation resistance in service. These performance requirements mainly depend on the yield ratio, that is, the ratio of yield strength to tensile strength. A lower yield ratio means larger deformation from the start of plastic deformation to the final fracture, which benefits formability. A higher yield ratio means higher plastic deformation resistance, which benefits service safety. In this paper, the mechanical properties and microstructure of the extruded 6013 aluminum alloy after natural aging, artificial aging, and retrogression re-aging are studied using microhardness tests, tensile tests, scanning electron microscopy, and transmission electron microscopy. The samples after the solid solution were naturally aged at room temperature and artificially aged at 170, 180, and 190 °C to determine the peak aging time. Then, after natural peak aging, the samples were heat-treated using the retrogression and re-aging process (retrogression at 200/210 °C for 0.5 h and re-aging at 170 °C). The results show that the tensile strength was 286 MPa, the yield strength was 158 MPa, and the yield ratio was 0.54 after natural peak aging for 16 d, which is suitable for plastic forming. The tensile strength was 362 MPa, the yield strength was 336 MPa, and the yield ratio reached 0.92 after the retrogression and re-aging process (retrogression at 210 °C for 0.5 h and peak re-aging at 170 °C for 2 h); the plastic deformation resistance was considerably enhanced. Compared with single-stage artificial aging, retrogression and re-aging can enhance the yield strength of 6013 aluminum alloy more substantially to break through the yield ratio limit in single-stage aging. Because the size of the precipitated phase decreases and the number density increases considerably after retrogression and re-aging, the precipitation strengthening effect is considerably enhanced. Precipitation strengthening has different effects on yield strength and tensile strength, so the yield strength ratio can be regulated by aging heat treatment. In other words, the plastic deformation and anti-deformation abilities of the alloy can be improved by natural peak aging and the retrogression and re-aging process, respectively.